Mathematics Education in the Early Years Results from the POEM2 Conference, 2014 - Meaney, Tamsin; Helenius, Ola; Johansson, Maria L.; Lange, Troels; Wernberg, Anna (Springer International Publishing : Imprint: Springer, 2016)
This book presents chapters based on papers presented at the second POEM conference on early mathematics learning. These chapters broaden the discussion about mathematics education in early childhood, by exploring the debate about construction versus instruction. Specific sections investigate the teaching and learning of mathematical processes and mathematical content, early childhood teacher development, transitions for young children between home and preschool, between home and school and between preschool and school. The chapters use a range of innovative theoretical and methodological approaches which will form an interesting basis for future research in this area.